Mutual Insurance Companies as Entities of the Social Economy Sector - Płonka, Maria (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article attempts to determine the position and distinguishing characteristics of mutual insurance companies (MICs) in the social economy. For this purpose, the broader context of the social economy sector in Poland, its distinguishing characteristics, and how it functions are outlined, and the position of MICs in the contemporary model social economy is indicated. The empirical section analyses the social and domestic aspects of MICs as entities in the social economy. The empirical study is qualitative, and subjective elements dominate. The following five aspects of social activity among nine MICs that existed in Poland in 2008 were researched: ‒ the structure and the area of social action, ‒ the people and organisation, ‒ the functioning of the organisation, ‒ its needs and problems, ‒ opinions and moods concerning the perception of the organisation. As a result, the analysis defines the position and character of MICs in the social economy in Poland.